The Relationships Between Weight Status and Physical Fitness Among Chinese Children and Youth. Issue 2 (3rd April 2019) - Zhang, Yunyun; Liu, Sichen; Li, Youfa; Li, Xin; Ren, Ping; Luo, Fang
ABSTRACT: Purpose : This study examined the prevalence of different weight status and the relationships between weight status and physical fitness among Chinese children and youth.Methods : Participants were 107, 206 Grade 4 children and 70, 213 Grade 8 youth from the China National Assessment of Educational Quality – Physical Education & Health in 2015 (CNAEQ-PEH 2015). Using World Health Organization (WHO) and US Centers for Disease Control and Prevention (CDC) criteria, weight status was divided into four groups (underweight, normal weight, overweight, and obese) according to Body Mass Index (BMI). The differences of physical fitness performances (15-m progressive aerobic cardiovascular endurance run [PACER], standing long jump, and 50-m sprint) among four weight status groups were compared. Data were analyzed using descriptive statistics, MANCOVA, and Cohen's d. Results : The prevalence of weight status varied by criteria (e.g., for Grade 4 boys, the prevalence of underweight by WHO and CDC were 5.9% and 10.5%; overweight were 14.5% and 11.4%, respectively). Compared with the normal weight group, the selected physical fitness performances in the overweight and obese groups were worse ( p < .001) with small to large effect sizes.Conclusion : The prevalence of underweight and overweight/obese was relatively high among Chinese children and youth. The prevalence of underweight, overweight, and obesity varied slightly depending on the criteria used for evaluating BMI. The overweight/obese participants tended to perform poorer in selected physical fitness tests. The performance disparities between the normal weight group and overweight/obese groups were larger in Grade 4 than in Grade 8 and among boys than among girls.